Ocean Literacy to Mainstream Ecosystem Services Concept in Formal and Informal Education: The Example of Coastal Ecosystems of Southern Portugal - Barracosa, Helena; de los Santos, Carmen B.; Martins, Márcio; Freitas, Cátia; Santos, Rui (Frontiers in Marine Science, 2019)
The concept of ecosystem services (ES) emerges as strategic to explain the influences that the ocean, and in particular coastal ecosystems, have on us and how we influence them back. Despite being a term coined several decades ago and being already wide-spread in the scientific community and among policy-makers, the ecosystem service concept still lacks recognition among citizens and educators. There is therefore a need to mainstream this concept in formal education and through Ocean Literacy resources. Although important developments in OL were done in the USA, particularly through the National Marine Educators Association (NMEA), this concept was only recently introduced in Europe. In Portugal, several informal OL education programs were developed in the last years, yet formal education on OL and, in particular, on ES is still very deficient. To address this limitation, the “Environmental Education Network for Ecosystem Services” (REASE), founded in 2017 in the Algarve region by a consortium of educational, environmental and scientific institutions, aims to increase OL through the dissemination of the perspective of how ES provided by coastal vegetation may contribute to the well-being of the populations. The projects and activities implemented by REASE focus mostly on formal-education of school children and include: 1) capacity building for K-12 teachers, 2) educational programs to support and develop ES projects in schools, including a citizen science project to evaluate blue carbon stocks in the Algarve, 3) the publication of a children’s book about the ES provided by the local Ria Formosa coastal lagoon, with a community-based participatory design (illustrations made by schoolchildren) and 4) a diverse array of informal education activities to raise awareness on the importance of coastal ecosystems on human well-being. REASE challenges are being successfully addressed by identifying threats to local coastal ecosystems that people worry about, and highlighting solutions to improve and maintain their health.